2021
DOI: 10.1161/strokeaha.120.034414
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Outcomes of Patients With Ischemic Stroke During COVID-19

Abstract: Background and Purpose: The coronavirus disease 2019 (COVID-19) pandemic has created challenges in the delivery of acute stroke care. In this study, we analyze the characteristics, evaluation, treatment, and in-hospital outcomes of patients presenting with acute ischemic stroke (AIS) pre-COVID-19 and during COVID-19. Methods: Get With The Guidelines-Stroke is a national registry of adults with stroke in the United States. Using this registry, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
3
25
1
2
Order By: Relevance
“…According to this finding, a similar proportion of cases with minor symptoms were hospitalized during the COVID-19 lockdowns. This is in accordance with the analysis of U.S. national inpatient stroke registry data on 81,084 patients with acute ischemic stroke who showed decreased hospitalizations and consistent median NIHSS scores during COVID-19 (4 February 2020 to 29 June 2020) compared to pre-pandemic period (1 November 2019 to 3 February 2020) ( 3 ). In contrast, an analysis of German health claims data found that patients with cerebral infarction or intracerebral hemorrhage more frequently suffered from hemiparesis or hemiplegia, speech impairment, swallowing difficulties, and hemispatial neglect ( 6 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to this finding, a similar proportion of cases with minor symptoms were hospitalized during the COVID-19 lockdowns. This is in accordance with the analysis of U.S. national inpatient stroke registry data on 81,084 patients with acute ischemic stroke who showed decreased hospitalizations and consistent median NIHSS scores during COVID-19 (4 February 2020 to 29 June 2020) compared to pre-pandemic period (1 November 2019 to 3 February 2020) ( 3 ). In contrast, an analysis of German health claims data found that patients with cerebral infarction or intracerebral hemorrhage more frequently suffered from hemiparesis or hemiplegia, speech impairment, swallowing difficulties, and hemispatial neglect ( 6 ).…”
Section: Discussionsupporting
confidence: 87%
“…In the months following the onset of the SARS-CoV-2 pandemic (COVID-19), a decrease in the number of patients with stroke admitted to hospitals was observed in several countries ( 1 , 2 ), which raised concerns about delays in adequate diagnosis and treatment of patients with stroke. Evaluation of a U.S. national inpatient stroke registry indicates a decline of acute ischemic stroke presentations of 15.3% in the period from the first week of February to the fourth week of June in 2020 when compared to the same weeks in 2019 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, overall, large studies show that there is similar door-to-CT, door-to-needle, and door-to-endovascular therapy times in the pre-COVID-19 era compared with the COVID-19 era. Additionally, there were no significant differences in the proportion of patients who received intravenous thrombolysis or endovascular therapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary and secondary stroke prevention guidelines should be implemented, and early rehabilitation should be started in the isolation area if feasible [ 32 ]. There have been reports of decreases in prescription of antithrombotics at discharge, dysphagia screening, smoking cessation counseling, stroke education, and rehabilitation consideration in COVID-19 and acute CVD patients [ 33 ]. It is important to remember the established practices in treating acute CVD, even in a complicated COVID-19 patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation